The best of Josh McDowell : a ready defense - McDowell, Josh; Wilson, Bill, 1948- (San Bernardino, CA : Here's Life, 1990)
Includes bibliographical references and indexes.
Keywords: Apologetics -- 20th century -- study and teaching